Can green credit policy under the concept of green economy curb corporate financialization to promote sustainable development? - Hu, Gongjin; Strielkowski, Wadim; Li, Hui; Zenchenko, Svetlana; Xu, Junwei (Frontiers in Environmental Science, 2023)
Under the concept of green economy, discovering how to utilize the Green Credit Guidelines in a way that guides enterprises to focus on their industries and to promote sustainable development has become an important and urgent objective. It is also conducive to the successful implementation of the “double-carbon target”. This paper uses Chinese A-share listed enterprises from 2007–2018 as its research object to explore whether green credit policy is conducive to reducing the financialization behavior of heavily polluting enterprises to curb their transformation from real to virtual. It is found that the financialization of heavily polluting enterprises has significantly decreased since the implementation of the Green Credit Guidelines in 2012, and these results remain unchanged after a series of robustness tests. A heterogeneity analysis shows that state-owned enterprises are subject to stronger policy effects than non-state-owned enterprises; furthermore, the studied policy effects are stronger in the eastern regions of China than in its central and western regions, and these effects are stronger in green provinces than in polluting provinces. A mechanism study finds that credit constraints and corporate innovation play a partially mediating role in the effect of green credit policy on corporate financialization. Further studies find that both the level of internal corporate governance and external monitoring contribute to the disincentivizing effect of green credit policy on financialization. Moreover, through an exploration of the possible economic consequences of the examined policy, it is found that the green credit policy reduces corporate financialization in favor of reducing inefficient corporate investment and major shareholders’ tunneling so that the level of corporate investor protection is improved. The findings validate the effectiveness of the Green Credit Guidelines and provide empirical evidence and empirical support for reducing corporate financialization to curb enterprises’ transformation from real to virtual and thus promoting the development of sustainability.